The Pivotal Role of Technopreneurship in Advancing Local Economic Development: A Comprehensive Literature Review on the Integration of Digitalization in Micro Agricultural Enterprises in Jambi (2020-2024) - Kurnianto Dwi Sugiranu; Alsa; Sindi Dwi Hartini; Definna Rahmadewi; Fina Rahmawati Wibowo (www.amertainstitute.com, 2025)
This article discusses the contribution of technopreneurship in building the local economy through a literature study on digitalization in micro enterprises in the agricultural sector in Jambi during 2020–2024. In practice, micro business actors still face a number of obstacles such as market limitations, low productivity, and lack of use of technology. The presence of technopreneurship brings a modern entrepreneurial approach based on technology, which not only digitizes business processes, but also increases the competitiveness of agricultural products through the use of digital platforms. Through a qualitative-descriptive approach that refers to academic literature, policy reports, and the latest data, this study finds that digital transformation facilitated by technopreneurship plays an important role in increasing the output, distribution, and income of microfarmers in Jambi. However, challenges in the form of infrastructure, limited digital literacy, and access to financing are still the main obstacles. Therefore, collaborative strategies from various stakeholders are needed so that the benefits of technopreneurship for local economic development can be optimized.